Kesejahteraan Ekonomi Masyarakat dalam Program Makan Bergizi Gratis Melalui Analisis Teori Utilitarianisme Jeremy Bentham - Annisa Luluk Firdausie (Jurnal Kajian dan Penelitian Umum, 2026)
This article aims to explain how the Indonesian government under the Prabowo–Gibran administration implements the Free Nutritious Meals (MBG) policy to promote community economic welfare from the perspective of Jeremy Bentham's utilitarianism. This study employs a qualitative method with a literature study analytical approach, seeking an in-depth understanding of the MBG program through comprehensive analysis of relevant academic sources and Jeremy Bentham's theory of utilitarianism. The findings indicate that the MBG program is consistent with Bentham's principle of "the greatest happiness for the greatest number," as it seeks to improve public welfare by providing nutritious meals for school children, pregnant women, and other vulnerable groups while simultaneously creating employment opportunities throughout the food production and distribution chain. These economic activities have the potential to reduce unemployment, stimulate local economies, and alleviate poverty in Indonesia. Furthermore, the program contributes to improving human capital through better nutrition, which may enhance educational outcomes and long-term productivity. From a utilitarian perspective, the MBG policy reflects a public policy that prioritizes the collective interests and welfare of the majority of society, in line with Indonesia's democratic principle of governance from, by, and for the people.